Kinase Activator-Receiver Preference in ErbB Heterodimers Is Determined by Intracellular Regions and Is Not Coupled to Extracellular Asymmetry - Ward, Matthew D. (J Biol Chem, 2015)
The EGF receptor (EGFR) family comprises four homologs in humans collectively known as the ErbB or HER proteins. ErbB proteins are receptor tyrosine kinases that become activated when ligands bind to their extracellular regions and promote formation of specific homo- and heterodimers with enhanced tyrosine kinase activity. An essential feature of ErbB activation is formation of an asymmetric kinase dimer in which the C-terminal lobe of one kinase serves as the activator or donor kinase by binding the N-terminal lobe of a receiver or acceptor kinase and stabilizing its active conformation. ErbB extracellular regions are also thought to form active asymmetric dimers in which only one subunit binds ligand. The observation that the unliganded ErbB2 kinase preferentially serves as the activator kinase when paired with EGFR/ErbB1 implied that extracellular asymmetry in ErbB proteins might be coupled to intracellular asymmetry with unliganded partners favoring the activator kinase position. Using cell-based stimulation assays and chimeric ErbB proteins, we show that extracellular asymmetry is not coupled to intracellular asymmetry and that ErbB intracellular regions are sufficient to determine relative kinase activator-receiver orientation. We further show a hierarchy of activator-receiver preferences among ErbB proteins, with EGFR/ErbB1 being the strongest receiver, followed by ErbB2 and then ErbB4, and that cis-phosphorylation of EGFR and ErbB2 appears to be negligible. This hierarchy shapes the nature of signaling responses to different ligands in cells expressing multiple ErbB proteins.